Reproducibility and changes in twitch properties associated with age and resistance training in young and elderly women - Cannon, J.; Kay, D.; Tarpenning, K. M.; Marino, F. E. (Scandinavian journal of medicine & science in sports, 2008)
We compared knee extensor twitch contractile properties (TP) between nine young women (YW, 20–30 years) and 10 elderly women (63–78 years) and examined changes associated with resistance training in addition to measurement reproducibility. Data were obtained on two occasions 3 weeks apart after which subjects performed bilateral leg extension and bilateral leg curl exercises 3 days/week for 10 weeks. TP demonstrated moderate to good reproducibility in both age groups with Pearson's r and the intra‐class correlation coefficient ranging from 0.67 to 0.85 (P<0.05) and the technical error of the measurement ranging from 4.2% to 7.8%. Pre‐training, peak twitch torque, rate of torque development, and the rate of relaxation were 24–32% greater for the YW than EW (P<0.05). Time to peak torque, half‐relaxation time, and contraction duration were not significantly different between age groups. Post‐training, changes of 2.6–6.1% were observed in TP; however, these changes were not significant in either group. These data suggest the presence of an age‐associated slowing in the rate of muscle contraction. Furthermore, the lack of change in TP in both groups suggests resistance training failed to alter contractile function. However, these findings are discussed in relation to measurement reproducibility and the meaningfulness of the data obtained.